Pengalaman Akseptor KB dalam Menggunakan KB Suntik 3 bulan di Puskesmas - Romauli, Suryati; Wijayanti, Ika; Wardhani, Yeni; Pasang, Novita (Jurnal Keperawatan Florence Nightingale, 2024)
The Three-Month Injectable Contraceptive (KB) is one of the highly effective contraceptive methods for preventing pregnancy, widely favored by couples of reproductive age. However, it also brings about some negative impacts that are complained about by acceptors. The purpose of this study is to explore the experiences of KB acceptors regarding the use of the Three-Month Injectable Contraceptive at the Libarek Primary Health Center in Jayawijaya Regency. This research utilizes a qualitative method with a phenomenological study approach. Data collection is carried out through in-depth interviews. The participants in this study consist of 10 individuals who have experience using the Three-Month Injectable Contraceptive and are selected using purposive sampling technique. The data collected, in the form of recordings and field notes, are analyzed using the colazzi technique. The results of this research yield five themes, namely, acceptor perceptions, reasons for acceptors choosing the Three-Month Injectable Contraceptive, advantages, complaints due to usage, and efforts made to address the impacts of the Three-Month Injectable Contraceptive. Acceptor perceptions of KB include preventing pregnancy and spacing births. Reasons for choosing the Three-Month Injectable Contraceptive include midwife recommendations, spousal support, practicality, and fear of other methods. The benefits of the Three-Month Injectable Contraceptive include not needing to take daily pills, maintaining a good appetite, injections every three months, no impact on breastfeeding, comfort, and safety. Complaints experienced by acceptors include menstrual cycle disturbances and weight changes. Efforts to address side effects include consulting with midwives, seeking information from friends, and adjusting eating patterns.